The deleterious impacts of code-switching and code-mixing among teenagers and secondary school students in the UAE - Mzeil, Ahmad Hammo (International Journal of Innovative Research and Scientific Studies, 2025)
With the global prominence of the English language as the language of instruction and communication, Emirati and Arab secondary school students in the United Arab Emirates are increasingly focusing on switching and swapping between Arabic and English in their daily conversations and interactions. The current study highlights the effects of Arabic-English code-switching and the occurrence of language interference among secondary school students in the United Arab Emirates. It draws attention to the drawbacks of this language shift and how it results not only in restraining the skills of language acquisition but also affects life, culture, and identity. In this research, 100 Emirati and Arab students, 50 boys and 50 girls, were randomly selected as participants in this survey. In addition, the same group of students also participated in answering a questionnaire regarding code-switching and code-mixing. The data collected from this group illustrated that code-switching can play a negative role in stifling the process of language learning and eventually weakening academic performance.